PENGARUH KETERJANGKAUAN HARGA, KUALITAS PRODUK, LOKASI, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN: Studi Kasus Pada Usaha Telur Bebek Calvin Farm - Calin, Calvin Valerian (Jurnal Manajemen dan Profesional, 2024)
The purpose of this research is to find out how price affordability, product quality, location and promotion influence the decision to purchase Calvin Farm duck eggs. Data processing was carried out using the SPSS 25 program and the sample in this study was obtained using the Slovin formula, which resulted in 100 respondents. Respondents in this research were consumers of Calvin Farm duck eggs. Based on the results of the analysis and discussion in the research that has been carried out, namely based on partial tests, it is stated that Price Affordability (X1), Product Quality (X2), Location (X3), and Promotion (X4) have a significant positive influence on Egg Purchase Decisions (Y). Calvin Farm ducks. Based on the simultaneous test, it is stated that price affordability, product quality, location and promotion together have a significant positive effect on the decision to purchase Calvin Farm duck eggs.